Cantharidin‐Induced Skin Blister as an In Vivo Model of Inflammation. Issue 2 (18th February 2021) - Dawson, Janet; Vogelsanger, Melanie
Abstract: The cantharidin‐induced skin blister is a simple model for investigating cell migration and inflammatory mediator production at a site of inflammation. Application of cantharidin solution to the ear pinna results in formation of a blister with cell influx and induction of inflammatory mediators at the skin site, as well as local swelling of the ear pinna. The model can be used for investigating anti‐inflammatory compounds, such as dexamethasone, and for preclinical drug discovery research, especially in areas where neutrophilic inflammation plays a role in disease pathophysiology. The cantharidin blister model is one of very few translational models described in humans, and the mechanism of inflammation induction is comparable in mice and man. In human studies, the cantharidin blister assay has been used to assess the effects of potential new therapies in early‐stage clinical studies. © 2021 Novartis AG. Basic Protocol 1 : Application of cantharidin to induce ear inflammation Basic Protocol 2 : Assessment of ear edema Basic Protocol 3 : Assessment of inflammatory mediators in ear tissue Basic Protocol 4 : Histological assessment of ear tissue